Variations in elemental and isotopic compositions of Cu, Zn, and Cd in mushrooms: are they site- or species-dependent? - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Anna Vynnychuk; Marketa Stepanova (Fungal Biology, 2026)

Jatulian mafic volcanics in the Segozero syncline, Karelian Craton: Implication for chronostratigraphy and timing of Lomagundi-Jatuli event in Fennoscandia - Alexandra V. Stepanova; Alexander V. Samsonov; Ekaterina B. Salnikova; Viktoria V. Ustinova; Maria A. Sukhanova; Yulia O. Larionova; Kseniya G. Erofeeva; Olga M. Silaeva; Oleg A. Maksimov; Anna A. Fateeva (Precambrian Research, 2026)

Study of Transplantation of Preparations Based on Fibrin Hydrogel and Olfactory Ensheathing Cells for Experimental Therapy of Spinal Cord Injuries - G. A. Fursa; A. I. Mukhina; A. V. Chadin; T. V. Kuznetsova; A. D. Voronova; E. K. Karsuntseva; V. S. Shishkina; A. A. Stepanenko; I. V. Reshetov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2026)

Analysis of the Ciliotoxic Effects of an Intranasal In Situ Ribavirin Delivery System: In Vitro and In Vivo Evaluation - I. B. Mikhel; E. O. Bakhrushina; D. N. Tikhonov; V. I. Shchekin; A. A. Nedorubov; O. I. Stepanova; I. I. Krasnyuk (Bulletin of Experimental Biology and Medicine, 2026)

Approaches to Identifying Neutrophil Extracellular Traps and Their Components in Preeclampsia - I. I. Stepanova; I. V. Byadovskaya; E. N. Plakhotina; T. N. Belousova; A. P. Aleksankin; A. A. Akhmetshina; V. I. Klaushuk; K. A. Artemeva; N. V. Nizyaeva; Yu. E. Dobrokhotova (Bulletin of Experimental Biology and Medicine, 2025)

The wild-grown Boletus edulis (penny bun) mushroom from the granite-based substrate: Trace elements uptake and Mg, Cu, Zn, and Cd isotope fractionations - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Marketa Stepanova (Fungal Biology, 2025)

Clinical Trials of Cell Products for the Treatment of Alzheimer’s Disease (Review) - A. D. Voronova; E. K. Karsuntseva; V. S. Shishkina; A. V. Chadin; G. A. Fursa; P. I. Gurin; T. V. Kuznetsova; I. V. Reshetov; S. V. Shport; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2025)

The Classical Matrigel Angiogenesis Model Revisited: Key Regulators and Comparative Analysis with 2D/3D Co-Culture Systems - I. B. Beloglazova; E. S. Zubkova; K. V. Dergilev; V. V. Stepanova; Yu. D. Goltseva; D. N. Penkov; Ye. V. Parfyonova (Bulletin of Experimental Biology and Medicine, 2025)

Changing isotope compositions of Mg, Ca and Sr in bulk crystalline rocks toward the weathering front: Disentangling inputs of geogenic base cations into ecosystems - Martin Novak; Yulia V. Erban Kochergina; Chris Holmden; Alexandre V. Andronikov; Vaclav Kachlik; Jana Kotkova; Irina E. Andronikova; James W. Kirchner; Jakub Hruška; Frantisek Veselovsky; Frantisek Laufek; Ondrej Pour; et al. (Applied Geochemistry, 2025)

Primary Progressive Aphasia in Neurological Practice - S. V. Kotov; M. M. Shcherbakova; G. T. Tonya; E. A. Stepanova; E. V. Isakova; V. A. Zenina (Neuroscience and Behavioral Physiology, 2025)

Estimation of irradiation doses in chicken samples using a reaction-based fingerprinting method - Anna V. Shik; Irina A. Stepanova; Marina V. Koksharova; Irina A. Doroshenko; Tatyana A. Podrugina; Ulyana A. Bliznyuk; Polina Yu. Borshchegovskaya; Alexander P. Chernyaev; Irina A. Ananieva; Igor A. Rodin; Mikhail K. Beklemishev (Food Chemistry, 2025)

Cell Therapy Is a New Treatment Option to Prevent Neurodegenerative Changes and Restore Cognitive Functions in Alzheimer’s Disease (Review) - A. D. Voronova; E. K. Karsuntseva; V. S. Shishkina; G. A. Fursa; A. V. Chadin; S. V. Shport; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2025)

Cytochrome C-Dependent Processes of Damage of Atherosclerotic Plaque Membranes Regulated by Anionic Phospholipids Containing Saturated and Unsaturated Fatty Acids - G. O. Stepanov; V. V. Volkov; S. P. Konukhova; A. A. Struchkova; Yu. A. Vladimirov; A. N. Osipov; A. V. Tarasov; R. S. Akchurin; D. M. Galyautdinov; V. P. Masenko; O. V. Stepanova (Bulletin of Experimental Biology and Medicine, 2025)

A methodology for creating collections of different focus of hairy roots - Anna Y. Stepanova; Evgeny A. Gladkov; Olga V. Gladkova (The Science of Nature, 2025)

Spatial and seasonal variability of Arctic phytoplankton communities in conditions of interaction with Atlantic origin waters in the St. Anna Trough (Kara Sea) - Valentina M. Sergeeva; Svetlana V. Stepanova; Mikhail V. Flint; Irina N. Sukhanova; Alexey V. Fedorov; Vladimir A. Artemiev (Journal of Marine Systems, 2025)

The Study of Cognitive Functions of Rats with Experimental Alzheimer’s Disease after Transplantation of Transduced Olfactory Ensheathing Cells Expressing Nerve Growth Factor - E. K. Karsuntseva; A. D. Voronova; V. S. Shishkina; V. Yu. Pokidko; A. I. Mukhina; A. V. Chadin; G. A. Fursa; A. V. Fedorov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2025)

Columnar jointing in Paleoproterozoic carbon-bearing rocks (Onega Basin, NW Russia): implications for carbon migration in sedimentary rocks - Svetlana Y. Chazhengina; Viktoria V. Ustinova; Alexandra V. Stepanova (International Geology Review, 2025)

Serum Markers of Abnormal Placental Attachment in Pregnant Women - K. A. Artemyeva; I. A. Kulikov; N. V. Nizyaeva; I. I. Stepanova; N. B. Tikhonova; L. M. Mikhaleva (Bulletin of Experimental Biology and Medicine, 2025)

Changes in Mg-Cu-Zn isotopic features in a system red cracking bolete – soil over an extended period - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova (Applied Geochemistry, 2025)

Application of Olfactory Ensheathing Cells in Collagen Hydrogels for Therapy of Experimental Spinal Cord Cysts - G. A. Fursa; A. I. Mukhina; A. V. Chadin; E. K. Karsuntseva; A. D. Voronova; V. S. Shishkina; P. A. Lazareva; A. A. Stepanenko; I. V. Reshetov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2025)

The Effect of Transplantation of Ensheathing Cells of the Olfactory Mucosa into the Hippocampal Area on the Restoration of Cognitive Abilities in Rats with Experimental Alzheimer’s Disease - E. K. Karsuntseva; A. D. Voronova; S. S. Andretsova; V. S. Shishkina; A. V. Chadin; G. A. Fursa; A. V. Fedorov; I. V. Reshetov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2024)

Effect of Compositionally Different Substrates on Elemental Properties of Bay Bolete Mushrooms: Case Study of 34 Essential and Non-essential Elements from Six Areas Affected Differently by Industrial Pollution - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova; Oksana Perehon (Biological Trace Element Research, 2024)
We studied concentrations of 34 essential and non-essential elements in samples of edible Bay Bolete ( Imleria badia ) mushrooms added by samples of the growing substrate and bioavailable fraction. The samples were collected from six forested sites affected differently by industrial pollution and underlain by compositionally contrasting bedrock: granite, amphibolite, and peridotite. In all cases, mushrooms behaved as a bioconcentrating system for elements such as Ag, K, P, Rb, S, and Se (BCF > 1) being a bioexcluding system for the rest of the elements analyzed (BCF < 1). Most analyzed elements displayed moderate to high within-mushroom mobility being accumulated preferably in the apical parts of the mushroom’s fruiting body (TF > 1). The highest mobility was demonstrated by Cd and Cu. Sodium was the only element with significantly low mobility (TF < 1), and it accumulated preferably in the stipe. Imleria badia seems to be sensitive to the accumulation of elements such as As, Cd, and Pb from the atmospheric deposits. Specific geochemistry of the growing substrate was reflected to different extend in the accumulation of elements such as Ag, Cu, Rb, S, Al, Ca, Fe, Ba, and Na in the mushroom’s fruiting bodies.

Transduced Olfactory Mucosa Cells Expressing Nerve Growth Factor for the Therapy of Experimental Spinal Cord Cysts - O. V. Stepanova; G. A. Fursa; S. S. Andretsova; E. K. Karsuntseva; V. S. Shishkina; A. V. Chadin; A. D. Voronova; A. S. Semkina; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2024)

The Use of Neurotrophic Factors as a Promising Strategy for the Treatment of Neurodegenerative Diseases (Review) - G. A. Fursa; S. S. Andretsova; V. S. Shishkina; A. D. Voronova; E. K. Karsuntseva; A. V. Chadin; I. V. Reshetov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2024)

Glucocorticoid Deflazacort Normalizes the Ultrastructure of Skeletal Muscles and the State of the Colon Microbiota in Dystrophin-Deficient Mice - M. V. Dubinin; I. B. Mikheeva; A. E. Stepanova; E. K. Pavlova; T. P. Gazheeva; K. N. Belosludtsev (Bulletin of Experimental Biology and Medicine, 2024)

Sizeable net export of base cations from a Carpathian flysch catchment indicates their geogenic origin while the 26Mg/24Mg, 44Ca/40Ca and 87Sr/86Sr isotope ratios in runoff are indistinguishable from atmospheric input - Martin Novak; Yulia V. Erban Kochergina; Alexandre V. Andronikov; Chris Holmden; Frantisek Veselovsky; Vaclav Kachlik; Jakub Hruška; Frantisek Laufek; Tomas Paces; Arnost Komarek; Ondrej Sebek; Marketa Stepanova; et al. (Environmental Science and Pollution Research, 2024)
Nutrient imbalances may negatively affect the health status of forests exposed to multiple stress factors, including drought and bark beetle calamities. We studied the origin of base cations in runoff from a small Carpathian catchment underlain by base-poor flysch turbidites using magnesium (Mg), calcium (Ca) and strontium (Sr) isotope composition of 10 ecosystem compartments. Our objective was to constrain conclusions drawn from long-term hydrochemical monitoring of inputs and outputs. Annual export of Mg, Ca and Sr exceeds 5-to-15 times their atmospheric input. Mass budgets per se thus indicate sizeable net leaching of Mg, Ca and Sr from bedrock sandstones and claystones. Surprisingly, δ 26 Mg, δ 44 Ca and 87 Sr/ 86 Sr isotope ratios of runoff were practically identical to those of atmospheric deposition and soil water but significantly different from bedrock isotope ratios. We did not find any carbonates in the studied area as a hypothetical, easily dissolvable source of base cations whose isotope composition might corroborate the predominance of geogenic base cations in the runoff. Marine carbonates typically have lower δ 26 Mg and 87 Sr/ 86 Sr ratios, and silicate sediments often have higher δ 26 Mg and 87 Sr/ 86 Sr ratios than runoff at the study site. Mixing of these two sources, if confirmed, could reconcile the flux and isotope data.

Combination cryoablation in patient with liver metastases - Dmitri A. Ionkin; Yulia A. Stepanova; Alexei V. Chzhao; A.A. Olifir; O.I. Zhavoronkova; N.A. Karelskaya (Cryobiology, 2024)

Pancreatic metastases cryosurgery - Alexei V. Chzhao; Dmitri A. Ionkin; Yulia A. Stepanova (Cryobiology, 2024)

Features of Remyelination after Transplantation of Olfactory Ensheathing Cells with Neurotrophic Factors into Spinal Cord Cysts - O. V. Stepanova; G. A. Fursa; E. K. Karsuntseva; S. S. Andretsova; A. V. Chadin; A. D. Voronova; V. S. Shishkina; A. S. Semkina; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2024)

Amorphous carbonaceous material in Paleoproterozoic pillow lavas (Onega Basin, NW Russia): Origin, source and migration - Svetlana Y. Chazhengina; Alexandra V. Stepanova; Viktoria V. Ustinova; Sergei A. Svetov (Lithos, 2023)

Dose-dependent effect of H2O2 on hairy roots of Scutellaria baicalensis: growth, composition of fatty acids, and flavones - A. I. Solov’eva; A. Y. Stepanova; T. V. Ivanova; A. S. Voronkov; Yu. M. Panov (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Accumulation and within-mushroom distribution of elements in red cracking bolete (Xerocomellus chrysenteron) collected over the extended period from compositionally contrasting substrates - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova (Environmental Monitoring and Assessment, 2023)
We conducted a study of elemental compositions of Xerocomellus chrysenteron samples accompanied by samples of related substrate soils. All samples were collected during the harvesting seasons 2021 and 2022 from three forested sites almost unpolluted by recent human activities and underlain by contrasting bedrock (granite, amphibolite, and serpentinite). Elements such as Ag, Cd, K, P, Rb, S, Se, and Zn were the main elements enriched in the mushroom’s fruiting bodies relative to the substrate. Concentrations of most elements in mushrooms were not site-dependent, with only Ag, As, Rb, and Se concentrations significantly depending on the bedrock composition. Some elements analyzed in mushrooms displayed temporal features, but such features were not systematic and varied for each element. Most analyzed elements were distributed unevenly within the mushroom’s fruiting bodies, with apical parts generally enriched in mobile elements. Mushrooms influenced concentrations of Ag, Cd, K, and Rb and a few other elements in the substrate via uptake, but such influence was very limited and can be responsible for only 2.5–11.5% of total depletion of the affected substrate in the named elements.

Separation of CH4 - CO2 gas mixture by gas hydrate crystallisation: A parametric study - Maria S. Kudryavtseva; Anton N. Petukhov; Dmitry N. Shablykin; Artem A. Atlaskin; Ekaterina A. Stepanova; Vladimir M. Vorotyntsev; Andrey V. Vorotyntsev (Gas Science and Engineering, 2023)

Modeling of Alzheimer’s Disease to Study the Efficacy of Cell Therapy (Review) - A. D. Voronova; E. K. Karsuntseva; O. V. Stepanova; A. V. Chadin; V. V. Shishkina; S. S. Andretsova; G. A. Fursa; S. V. Shport; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2023)

Spatial and temporal trends in δ66Zn and 206Pb/207Pb isotope ratios along a rural transect downwind from the Upper Silesian industrial area: Role of legacy vs. present-day pollution - Eva Prechova; Ondrej Sebek; Martin Novak; Alexandre V. Andronikov; Ladislav Strnad; Vladislav Chrastny; Jerzy Cabala; Marketa Stepanova; Jan Pasava; Eva Martinkova; Petra Pacherova; Vladimir Blaha; et al. (Environmental Pollution, 2023)

Application of Behavioral Tests for Evaluation of an Experimental Model of Alzheimer’s Disease in Female Rats - E. K. Karsuntseva; A. D. Voronova; A. V. Chadin; V. V. Shishkina; G. A. Fursa; S. S. Andretsova; I. V. Reshetov; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2023)

Elemental and Cu–Zn isotopic compositions of two bolete mushrooms grown on contrasting substrates - Alexandre V. Andronikov; Irina E. Andronikova; Ondrej Sebek; Eva Martinkova; Marketa Stepanova; Hyacinta Vitkova; Elena Antalova (Applied Geochemistry, 2023)

Translocation of elements and fractionation of Mg, Cu, Zn, and Cd stable isotopes in a penny bun mushroom (Boletus edulis) from western Czech Republic - Alexandre V. Andronikov; Irina E. Andronikova; Eva Martinkova; Ondrej Sebek; Marketa Stepanova (Environmental Science and Pollution Research, 2023)
Boletus edulis mushroom behaved as an accumulating biosystem with respect to Ag, Rb, Zn, and K. The mushroom was not an efficient accumulator of toxic As, Pb, and Cr, but Se and Cd displayed much higher concentrations in the mushroom than in the substrate samples. Other elements were bioexclusive. Different elements had different within-mushroom mobilities. The highest mobilities were displayed by Zn and Ag, and the lowest by Ti. The mushroom’s fruiting body preferentially took up lighter Mg, Cu, and Cd isotopes (Δ 26 Mg FB-soil = −0.75‰; Δ 65 Cu FB-soil = −0.96‰; Δ 114 Cd FB-soil = −0.63‰), and the heavier 66 Zn isotope (Δ 66 Zn FB-soil = 0.92‰). Positive within-mushroom Zn isotope fractionation resulted in accumulation of the heavier 66 Zn (Δ 66 Zn cap-stipe = 0.12‰) in the mushroom’s upper parts. Cadmium displayed virtually no within-mushroom isotope fractionation. Different parts of the fruiting body fractionated Mg and Cu isotopes differently. The middle part of the stipe (3–6 cm) was strongly depleted in the heavier 26 Mg with respect to the 0–3 cm (Δ 26 Mg stipe(3–6)-stipe(0–3) = −0.73‰) and 6–9 cm (Δ 26 Mg stipe(6–9)-stipe(3–6) = 0.28‰) sections. The same stipe part was strongly enriched in the heavier 65 Cu with respect to the 0–3 cm (Δ 65 Cu stipe(3–6)-stipe(0–3) = 0.63‰) and 6–9 cm (Δ 65 Cu stipe(6–9)-stipe(3–6) = −0.42‰) sections. An overall tendency for the upper mushroom’s parts to accumulate heavier isotopes was noted for Mg (Δ 26 Mg cap-stipe = 0.20‰), Zn (Δ 66 Zn cap-stipe = 0.12‰), and Cd (Δ 114 Cd cap-stipe = 0.04‰), whereas Cu showed the opposite trend (Δ 65 Cu cap-stipe = −0.08‰).

Obtaining a New Gene-Cell Construct Based on Transduced Olfactory Ensheathing Cells for the Treatment of Spinal Cord Injuries - A. D. Voronova; A. O. Sosnovtseva; O. V. Stepanova; A. V. Chadin; E. K. Karsuntseva; G. A. Fursa; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2022)

Determination of the Prevalence of Postcovid Syndrome and Assessment of the Effectiveness of the Drug Cortexin in the Treatment of Neurological Disorders in Patients with Postcovid Syndrome. Results of the CORTEX Multicenter Clinical and Epidemiological Observational Program - M. V. Putilina; Z. Yu. Mutovina; O. V. Kurushina; D. M. Khalilova; E. N. Saverskaya; S. B. Stepanova; M. A. Khoreva; A. S. Starikov (Neuroscience and Behavioral Physiology, 2022)

Neurotrophin-3 Enhances the Effectiveness of Cell Therapy in Chronic Spinal Cord Injuries - O. V. Stepanova; A. D. Voronova; A. V. Chadin; G. A. Fursa; E. K. Karsuntseva; M. P. Valikhov; A. S. Semkina; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2022)

An Optoelectronic Spectral Sensor for Monitoring the Elimination of Uremic Markers with Low and Middle Molecular Weight during Hemodialysis Therapy - G. A. Zemchenkov; G. A. Konoplev; V. Korsakov; A. I. Kuznetsov; N. V. Roshchina; O. S. Stepanova; A. Frorip (Biomedical Engineering, 2022)

Changes in the Expression of Pluripotency Factor Oct-4 and Intensity of Apoptosis in the Uterus during Spontaneous and Immune-Dependent Abortions in Mice - K. A. Artem’eva; I. I. Stepanova; I. M. Bogdanova; M. N. Boltovskaya; N. V. Yaglova; S. V. Obernikhin; E. A. Ponomarenko (Bulletin of Experimental Biology and Medicine, 2022)

Application of a New Gene-Cell Construct Based on the Olfactory Mucosa Escheating Cells Transduced with an Adenoviral Vector Encoding Mature BDNF in the Therapy of Spinal Cord Cysts - E. K. Karsuntseva; G. A. Fursa; A. O. Sosnovtseva; A. D. Voronova; A. V. Chadin; A. S. Semkina; O. V. Stepanova; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2022)

The foraminiferal zonal scale of the Devonian–Carboniferous boundary beds in Russia and Western Kazakhstan and its correlation with ammonoid and conodont scales - Elena I. Kulagina; Elena L. Zaytseva; Yadviga A. Vevel; Tatiana I. Stepanova; Nilyufer B. Gibshman; Svetlana V. Nikolaeva; Lyudmila I. Kononova; Artem N. Plotitsyn (Palaeobiodiversity and Palaeoenvironments, 2021)

The Effect of Transplantation of Olfactory Ensheathing Cells on the Size of Posttraumatic Spinal Cord Cysts - A. D. Voronova; O. V. Stepanova; A. V. Chadin; G. A. Fursa; E. K. Karsuntseva; M. P. Valikhov; А. S. Semkina; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2021)

Behaviour of Cr in runoff from two catchments underlain by felsic bedrock - A. V. Andronikov; M. Novak; P. Kram; O. Sebek; I. E. Andronikova; N. A. Efremenko; G. S. Borodulina; D. A. Subetto; M. Stepanova; E. Antalova; M. A. Levichev; M. V. Zobkova; et al. (Hydrological Sciences Journal, 2020)

Preparation of Adhesion Culture of Neural Stem/Progenitor Cells of the Olfactory Mucosa for the Treatment of Spinal Cord Injuries - O. V. Stepanova; A. D. Voronova; G. A. Fursa; E. K. Karsuntseva; M. P. Valikhov; A. V. Chadin; D. A. Vishnevskii; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2020)

Correlation of endogenous β-glucuronidase activity with differentiation of in vitro cultures of Scutellaria baicalensis - A. I. Solov’eva; S. V. Evsyukov; R. A. Sidorov; A. Yu. Stepanova (Acta Physiologiae Plantarum, 2020)

Combined Preparation of Human Olfactory Ensheathing Cells in the Therapy of Post-Traumatic Cysts of the Spinal Cord - A. D. Voronova; O. V. Stepanova; M. P. Valikhov; A. V. Chadin; A. S. Semkina; E. K. Karsuntseva; G. A. Fursa; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2020)

Proliferative Activity of Mouse Splenocytes in Physiological Pregnancy and in Models of Spontaneous and Muramylpeptide-Dependent Abortions - K. A. Artem’eva; M. N. Boltovskaya; I. M. Bogdanova; S. S. Obernikhin; I. I. Stepanova; A. A. Stepanov; O. A. Svitich; O. V. Kalyuzhin (Bulletin of Experimental Biology and Medicine, 2020)

Araucarioid wood from the late Oligocene–early Miocene of Hainan Island: first fossil evidence for the genus Agathis in the Northern Hemisphere - Alexei A. Oskolski; Luliang Huang; Anna V. Stepanova; Jianhua Jin (Journal of Plant Research, 2020)

Genetic Basis of Attenuation of Cold-Adapted Influenza Strain B/Leningrad/14/17/55 — Backup Master Donor Virus for Influenza Type B Live Attenuated Vaccines - E. V. Krutikova; E. A. Stepanova; P. F. Wong; I. V. Kiseleva; E. P. Grigor’eva; L. G. Rudenko (Bulletin of Experimental Biology and Medicine, 2020)

Energy Metabolism in Cellular Regenerative Processes: Focus on PPARα - T. G. Kulikova; O. V. Stepanova; A. D. Voronova; M. P. Valikhov; T. V. Kuznetsova; E. V. Kurilina; R. S. Akchurin; I. V. Reshetov; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2020)

BAL fluid analysis in the identification of infectious agents in patients with hematological malignancies and pulmonary infiltrates - P. Zak; E. Vejrazkova; A. Zavrelova; L. Pliskova; L. Ryskova; P. Hubacek; V. Stepanova; M. Kostal; V. Koblizek; P. Paterova; Jakub Radocha (Folia Microbiologica, 2020)

Neural Stem/Progenitor Cells of Human Olfactory Mucosa for the Treatment of Chronic Spinal Cord Injuries - A. D. Voronova; O. V. Stepanova; M. P. Valikhov; A. V. Chadin; A. S. Semkina; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2020)

Comparison of the Efficiency of Transplantation of Rat and Human Olfactory Ensheathing Cells in Posttraumatic Cysts of the Spinal Cord - А. D. Voronova; O. V. Stepanova; M. P. Valikhov; A. V. Chadin; А. S. Semkina; M. A. Abakumov; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2019)

Experimental Study of Genetic Constellation of Cold-Adapted Master Donor Viruses for Live Attenuated Influenza Vaccine Type B - E. V. Krutikova; E. A. Stepanova; I. V. Kiseleva; L. G. Rudenko (Bulletin of Experimental Biology and Medicine, 2019)

Use of Hydrobionts as Alternative Biological Models - G. I. Pronina; N. Yu. Koryagina; A. O. Revyakin; O. I. Stepanova; Zh. O. Kurishenko; N. V. Petrova (Neuroscience and Behavioral Physiology, 2019)

Interaction of NK Cells, Trophoblast, and Endothelial Cells during Angiogenesis - K. L. Belyakova; O. I. Stepanova; A. R. Sheveleva; V. A. Mikhailova; D. I. Sokolov; S. A. Sel’kov (Bulletin of Experimental Biology and Medicine, 2019)

Amino Acid Substitutions N123D and N149D in Hemagglutinin Molecule Enhance Immunigenicity of Live Attenuated Influenza H7N9 Vaccine Strain in Experiment - E. A. Stepanova; T. S. Kotomina; V. A. Matyushenko; T. A. Smolonogina; V. S. Shapovalova; L. G. Rudenko; I. N. Isakova-Sivak (Bulletin of Experimental Biology and Medicine, 2019)

Survival and Migration of Rat Olfactory Ensheathing Cells after Transplantation into Posttraumatic Cysts in the Spinal Cord - A. D. Voronova; M. P. Valikhov; O. V. Stepanova; P. A. Mel’nikov; A. V. Chadin; K. N. Sidoruk; A. S. Semkina; M. A. Abakumov; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2018)

Development of Pyrosequencing Assay for Evaluation of Genetic Stability of Vaccine Strains of Live Attenuated Influenza Type B Vaccine - E. А. Stepanova; E. V. Krutikova; I. V. Kiseleva; V. A. Vasil’eva; L. G. Rudenko (Bulletin of Experimental Biology and Medicine, 2018)

Isolation of Rat Olfactory Ensheathing Cells and Their Use in the Therapy of Posttraumatic Cysts of the Spinal Cord - O. V. Stepanova; А. D. Voronova; A. V. Chadin; M. P. Valikhov; M. A. Abakumov; I. V. Reshetov; V.P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2018)

Pathological Remodeling of the Myocardium in Chronic Heart Failure: Role of PGC-1α - T. G. Kulikova; O. V. Stepanova; A. D. Voronova; M. P. Valikhov; V. N. Sirotkin; I. V. Zhirov; S. N. Tereshchenko; V. P. Masenko; A. N. Samko; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2018)

Preparation of Human Olfactory Ensheathing Cells for the Therapy of Spinal Cord Injuries - А. D. Voronova; O. V. Stepanova; M. P. Valikhov; A. V. Chadin; А. S. Dvornikov; I. V. Reshetov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2018)

Involvement of the Urokinase Receptor and Its Endogenous Ligands in the Development of the Brain and the Formation of Cognitive Functions - E. V. Semina; K. A. Rubina; V. V. Stepanova; V. A Tkachuk (Neuroscience and Behavioral Physiology, 2018)

Interfacial Electrostatic Properties of Hydrated Mesoporous and Nanostructured Alumina Powders by Spin Labeling EPR - Elena G. Kovaleva; Leonid S. Molochnikov; Darya P. Stepanova; Alexander V. Pestov; Dmitrii G. Trofimov; Igor A. Kirilyuk; Alex I. Smirnov (Cell Biochemistry and Biophysics, 2017)

A Study of the Protective Properties of an Antibody-Based Antidote Metabolizing Organophosphorus Pesticide Paraoxon - Yu. A. Mokrushina; A. V. Stepanova; V. A. Palikov; A. V. Stepanov; G. I. Belous; I. A. Dyachenko; V. D. Knorre; I. V. Smirnov; A. G. Gabibov (Bulletin of Experimental Biology and Medicine, 2017)

Effect of Cytokines on the Formation Tube-Like Structures by Endothelial Cells in the Presence of Trophoblast Cells - D. I. Sokolov; T. Yu. Lvova; L. S. Okorokova; K. L. Belyakova; A. R. Sheveleva; O. I. Stepanova; V. A. Mikhailova; S. A. Sel’kov (Bulletin of Experimental Biology and Medicine, 2017)

Experimental Study of a Radiopharmaceutical Agent Based on Modified Fatty Acid Labeled with Technetium-99m - S. I. Sazonova; Yu. N. Il’yushenkova; Yu. B. Lishmanov; S. V. Tsibul’nikov; V. S. Skuridin; E. A. Nesterov; N. V. Varlamova; E. A. Il’ina; V. D. Filimonov; M. V. Belyanin; E. V. Stepanova; S. M. Minin (Bulletin of Experimental Biology and Medicine, 2017)

New Genetic Constructs for Generation of Stable Therapeutic Antibodies to Organophosphorus Toxins in Methylotrophic Yeasts Pichia Pastoris - Yu. A. Mokrushina; A. V. Stepanova; T. V. Bobik; I. V. Smirnov; A. G. Gabibov (Bulletin of Experimental Biology and Medicine, 2016)

Detection of Antileukocytic Antibodies in Blood Serum using Lymphocytes and Latex Microspheres Carrying HLA-Antigens upon Alloimmunization of Women with Recurrent Pregnancy Loss - E. O. Stepanova; M. A. Nikolaeva; E. L. Golubeva; V. V. Vtorushina; L. V. Van’ko; Z. S. Khodzhaeva; L. V. Krechetova (Bulletin of Experimental Biology and Medicine, 2016)

Antiangiogenic Activity of Alofanib, an Allosteric Inhibitor of Fibroblast Growth Factor Receptor 2 - D. A. Khochenkov; E. Sch. Solomko; N. M. Peretolchina; O. O. Ryabaya; E. V. Stepanova (Bulletin of Experimental Biology and Medicine, 2015)

Dual-Wavelength Optoelectronic Sensor for Monitoring Uric Acid Concentration in Dialysate - A. M. Vasilevsky; R. P. Gerasimchuk; A. Yu. Zemchenkov; G. A. Konoplev; A. V. Rubinsky; O. S. Stepanova; A. A. Frorip (Biomedical Engineering, 2015)

Detection of Antibodies In Vitro Binding to Endothelial Cells in the Sera from Women with Normal Pregnancy and Preeclampsia - M. M. Ziganshina; M. A. Nikolaeva; E. O. Stepanova; L. V. Krechetova; N. E. Kan; D. I. Sokolov; S. A. Sel’kov; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2015)

Effect of Monocyte-Like THP-1 Cells on the Formation of Vascular Tubes by EA.Hy926s Endothelial Cells in the Presence of Cytokines - T. Yu. L’vova; O. I. Stepanova; L. S. Okorokova; V. A. Semenov; E. A. Rebezova; S. A. Sel’kov; D. I. Sokolov (Bulletin of Experimental Biology and Medicine, 2015)

Response of Hemopoietic, Progenitor, and Multipotent Mesenchymal Stromal Cells to Administration of Ketanserin during Pulmonary Fibrosis - A. M. Dygai; E. G. Skurikhin; O. V. Pershina; I. E. Stepanova; E. S. Khmelevskaya; N. N. Ermakova; A. M. Reztsova; V. A. Krupin; D. V. Reikhart; V. E. Goldberg (Bulletin of Experimental Biology and Medicine, 2014)

Humic Substances Enhance Growth and Respiration in the Basidiomycetes Trametes Maxima Under Carbon Limited Conditions - Olga I. Klein; Elena P. Isakova; Yulia I. Deryabina; Natalia A. Kulikova; Gennadii A. Badun; Maria G. Chernysheva; Elena V. Stepanova; Olga V. Koroleva (Journal of Chemical Ecology, 2014)

Effect of Spiperone on Mesenchymal Multipotent Stromal and Hemopoietic Stem Cells under Conditions of Pulmonary Fibrosis - E. G. Skurikhin; E. S. Khmelevskaya; N. N. Ermakova; O. V. Pershina; A. M. Reztsova; V. A. Krupin; I. E. Stepanova; V. M. Reztsova; D. V. Reikhart; A. M. Dygai (Bulletin of Experimental Biology and Medicine, 2014)

Effect of Immobilized Hyaluronidase on Stem and Progenitor Cells in Pulmonary Fibrosis - A. M. Dygai; E. G. Skurikhin; E. S. Khmelevskaya; N. N. Ermakova; A. M. Reztsova; O. V. Pershina; V. A. Krupin; I. E. Stepanova; V. M. Reztsova; A. V. Artamonov; A. A. Bekarev; P. G. Madonov; et al. (Bulletin of Experimental Biology and Medicine, 2014)

Anti-Inflammatory and Antifibrotic Effects of a Combination of Spiperone and Immobilized Hyaluronidase on Partially Reversible and Irreversible Toxic Pneumofibrosis - E. G. Skurikhin; N. N. Ermakova; A. M. Reztsova; O. V. Pershina; E. S. Khmelevskaya; V. A. Krupin; I. E. Stepanova; V. M. Reztsova; D. V. Reihard; A. V. Artamonov; A. A. Bekarev; P. G. Madonov; et al. (Bulletin of Experimental Biology and Medicine, 2013)

Antifibrotic Effects of Immobilized Hyaluronidase in Repeated Bleomycin-Induced Lesions of the Alveolar Epithelium - A. M. Dygai; E. G. Skurikhin; N. N. Ermakova; A. M. Reztsova; O. V. Pershina; E. S. Khmelevskaya; V. A. Krupin; I. E. Stepanova; V. M. Reztsova; A. V. Artamonov; A. A. Bekarev; P. G. Madonov; et al. (Bulletin of Experimental Biology and Medicine, 2013)

New Features in the Subsurface Structure Model of El Hierro Island (Canaries) from Low-Frequency Microseismic Sounding: An Insight into the 2011 Seismo-Volcanic Crisis - A. V. Gorbatikov; F. G. Montesinos; J. Arnoso; M. Yu Stepanova; M. Benavent; A. A. Tsukanov (Surveys in Geophysics, 2013)

Differentiation of Mesenchymal Multipotent Stromal Cells of the Lungs in Pneumofibrosis - E. G. Skurikhin; E. S. Khmelevskaya; O. V. Pershina; N. N. Ermakova; V. A. Krupin; A. M. Reztsova; L. A. Ermolaeva; V. D. Yakushina; I. E. Stepanova; V. M. Reztsova; N. V. Cherdyntseva; M. N. Stakheeva; et al. (Bulletin of Experimental Biology and Medicine, 2013)

Antifibrotic Effect of Combined Treatment with Neuroleptic Drug and Immobilized Hyaluronidase in Pulmonary Fibrosis - A. M. Dygai; E. G. Skurikhin; N. N. Ermakova; O. V. Pershina; V. A. Krupin; A. M. Reztsova; L. A. Ermolaeva; E. S. Khmelevskaya; I. E. Stepanova; A. V. Artamonov; A. A. Bekarev; P. G. Madonov; et al. (Bulletin of Experimental Biology and Medicine, 2013)

Optimal Detection of Serum Antipaternal Antileukocytic Antibodies after Injection of Allogenic Lymphocytes in Women with Habitual Abortions - L. V. Krechetova; M. A. Nikolaeva; L. V. Van’ko; M. M. Ziganshina; E. L. Golubeva; E. O. Stepanova; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2012)

Mechanisms of the Anti-Infl ammatory and Antifi brotic Activity of a Sympatholytic Agent during Toxic Pulmonary Fibrosis - E. G. Skurikhin; E. S. Khmelevskaya; O. V. Pershina; T. V. Andreeva; L. A. Ermolaeva; V. A. Krupin; N. N. Ermakova; A. M. Reztsova; I. E. Stepanova; A. M. Dygai (Bulletin of Experimental Biology and Medicine, 2012)

Antifibrotic and Anti-Inflammatory Activity of a Neuroleptic Drug on the Model of Pulmonary Fibrosis - A. M. Dygai; E. G. Skurikhin; T. V. Andreeva; O. V. Pershina; L. A. Ermolaeva; E. S. Khmelevskaya; V. A. Krupin; A. M. Reztsova; I. E. Stepanova (Bulletin of Experimental Biology and Medicine, 2012)

Effect of Antiserotonin Drug on the Development of Lung Fibrosis and Blood System Reactions after Intratracheal Administration of Bleomycin - E. G. Skurikhin; T. V. Andreeva; E. S. Khmelevskaya; L. A. Ermolaeva; O. V. Pershina; V. A. Krupin; N. N. Ermakova; A. M. Reztsova; I. E. Stepanova; V. E. Gol’dberg; A. M. Dygai (Bulletin of Experimental Biology and Medicine, 2012)

Myosin-activating protein kinases are possible regulators of nonmuscle myosin in developing human heart - O. V. Stepanova; A. V. Chadin; A. G. Masyutin; T. G. Kulikova; R. A. Poltavceva; V. P. Masenko; G. T. Sukhikh (Bulletin of Experimental Biology and Medicine, 2011)

Reactions of the blood system and stem cells in bleomycin-induced model of lung fibrosis - A. M. Dygai; E. G. Skurikhin; T. V. Andreeva; L. A. Ermolaeva; E. S. Khmelevskaya; O. V. Pershina; V. A. Krupin; A. M. Reztsova; I. E. Stepanova; V. E. Goldberg (Bulletin of Experimental Biology and Medicine, 2011)

On the role of carbohydrate-protein highly selective interactions in the biological activity of glycoconjugates: Grifola frondosa (Fr.) S.F. Gray lectin binding to specific and non-specific antibodies - Lada V. Stepanova; Gennady L. Burygin; Valentina E. Nikitina; Olga M. Tsivileva (World Journal of Microbiology and Biotechnology, 2011)

Seafloor Massive Sulfides from the Northern Equatorial Mid-Atlantic Ridge: New Discoveries and Perspectives - G. Cherkashov; I. Poroshina; T. Stepanova; V. Ivanov; V. Bel'tenev; L. Lazareva; I. Rozhdestvenskaya; M. Samovarov; V. Shilov; G. P. Glasby; Y. Fouquet; V. Kuznetsov (Marine Georesources & Geotechnology, 2010)

Regulatory Mechanisms for Apoptosis in Placental Tissue during Normal Pregnancy and Gestosis-Complicated Pregnancy - D. I. Sokolov; A. V. Kolobov; M. V. Lesnichija; I. N. Kostiouchek; O. I. Stepanova; I. M. Kvetnoy; S. A. Selkov (Bulletin of Experimental Biology and Medicine, 2009)

Two New Hydrothermal Fields at the Mid-Atlantic Ridge - G. Cherkashov; V. Bel'tenev; V. Ivanov; L. Lazareva; M. Samovarov; V. Shilov; T. Stepanova; G. P. Glasby; V. Kuznetsov (Marine Georesources & Geotechnology, 2008)

Effects of prenatal and neonatal cadmium intoxication on the intensity of lipid peroxidation and activity of glutathione system in progeny of albino rats - O. V. Slyuzova; E. V. Stepanova; A. D. Temraleeva; R. A. Kireev; V. V. Ignatov (Bulletin of Experimental Biology and Medicine, 2008)

Application of multipotent mesenchymal stromal cells from human adipose tissue for compensation of neurological deficiency induced by 3-nitropropionic acid in rats - A. V. Kulikov; M. S. Stepanova; S. L. Stvolinsky; R. M. Hudoerkov; D. N. Voronkov; A. A. Rzhaninova; D. V. Goldstein; A. A. Boldyrev (Bulletin of Experimental Biology and Medicine, 2008)

Mutant C57Bl/KsLeprdb/+ mice as a genetic model of type 2 diabetes mellitus - O. I. Stepanova; N. N. Karkischenko; O. V. Baranova; T. V. Galahova; X. X. Semenov; T. B. Beskova; E. A. Stepanova; A. R. Zakir’yanov; N. A. Onischenko (Bulletin of Experimental Biology and Medicine, 2007)

Creation of a gelatin-based solution for preservation of leukocytes - E. P. Svedentsov; E. S. Stepanova; T. V. Tumanova; O. O. Zaytseva; O. N. Solomina (Bulletin of Experimental Biology and Medicine, 2007)

X-ray structural studies of the fungal laccase from Cerrena maxima - Andrey V. Lyashenko; Isabel Bento; Viatcheslav N. Zaitsev; Nadezhda E. Zhukhlistova; Yuliya N. Zhukova; Azat G. Gabdoulkhakov; Ekaterina Y. Morgunova; Wolfgang Voelter; Galina S. Kachalova; Elena V. Stepanova; Ol`ga V. Koroleva; Victor S. Lamzin; et al. (JBIC Journal of Biological Inorganic Chemistry, 2006)

Development of differential sensitivity of CaOv ovarian adenocarcinoma cells to antitumor agents under conditions of hypoxia - O. V. Pavlichenko; A. N. Shishkin; E. V. Stepanova; T. K. Dubovaya; M. A. Krasil’nikov (Bulletin of Experimental Biology and Medicine, 2006)

Store-Dependent Entry of Ca2+ into Sensory Neurons of the Rat - I. V. Stepanova (Neurophysiology, 2005)

Direction of fluid transport in the lens - L. V. Stepanova; I. Yu. Marchenko; G. M. Sychev (Bulletin of Experimental Biology and Medicine, 2005)

Intracellular mechanisms participating in the formation of neuronal calcium signals - E. P. Kostyuk; P. G. Kostyuk; I. V. Stepanova (Neurophysiology, 2004)

Analytical Assessment of the Effect of Changes in Peripheral Blood Parameters on the State of the Human Body and Its Systems - V. A. Kovyazin; L. A. Stepanova; L. A. Lebedev; R. V. Stavitskii; M. K. Stavitskaya; M. V. Kravchenko; I. M. Lebedenko (Biomedical Engineering, 2004)

Changes in Lymph Microcirculation during Pathological Stress - A. V. Solov'eva; E. I. Galanzha; T. V. Stepanova; G. E. Brill' (Bulletin of Experimental Biology and Medicine, 2002)

Accumulation of Mutagenic Xenobiotics in Fresh Water (Lake Baikal) and Marine (Hornoya Island) Ecosystems - Ludmila I. Stepanova; Vadim M. Glaser; Tatiana I. Savinova; Sergey V. Kotelevtsev; Demetris Savva (Ecotoxicology, 1999)

The role of urokinase in cell migration induced by growth factors - V. V. Stepanova; A. Bobik; S. P. Domogatskii; S. A. Mukhina; V. A. Tkachuk (Bulletin of Experimental Biology and Medicine, 1999)